Danzu, contemporary dance and the spiral of the student process. - Betancourt Villa, Diana (2021)
We present here the work of Danzú, an alternative group of Contemporary Dance at the University of Costa Rica. This group incorporates the spiral movement as an essential method for the development of the creative process and the body. Each year a question is posed, which by means of exploring movements and the creative process, generates a choreography. The consequences of this student process, offers opportunities for growth, the joy of living, the connection with the body as to elicit the awakening of consciousness to promote healing, focusing on the present, gathering strength from the essence of each one.